Revitalization of the Mgmp Program to Improve the Pedagogic Competence of High School Science Teachers (SMA) - Munajat, Salim; Wasliman, Iim; Suhendraya Muchtar, Hendi; Iriantara, Yosal (International Journal of Educational Research & Social Sciences, 2022)
The Subject Teacher Conference (MGMP) as an association or association of teachers plays a strategic role in improving and strengthening teacher competence through discussion and training. Its main role is to facilitate teachers in the same field of study in exchanging opinions and experiences. However, there are still many teachers who are not active so that they do not develop and are static even though they have participated in MGMP activities. In addition, due to the limited number of roles that can be performed by the MGMP, the ability of teachers to teach as indicated by the indicators of student success is still low. The purpose of this study was to find out how "the revitalization of the MGMP Program To Improve the Pedagogic Competence of Science Teachers at SMA in Karawang Regency is actually through the "POAC" management theory approach from GR Terry. In particular, this study describes and analyzes (1) planning, (2) organizing, (3) implementing and (4) assessing the MGMP in science subjects. This study uses a qualitative method with a case study approach. Collecting data by conducting observations, interviews, and documentation studies as well as validation of research results. The results of the study indicate that the MGMP Revitalization Program is a classification of the findings from the identification process of the MGMP Revitalization Program which is carried out specifically so that the profile obtained in the MGMP is based on factual, objective and precise data. The follow up in the MGMP Program Revitalization lies in understanding the teacher team and how they must coordinate, cooperate and follow up when handling MGMP.